The dental equipment industry in Brazil: origin, structure, and transformations of the space of the dominant companies (Research, Society and Development, 2022)
Starting from the theoretical formulations of Pierre Bourdieu about the economic sociology, this study analyzed the origin, structure and transformations of the dental equipment industry in Brazil. It is an exploratory study, based on documentary analysis of company websites, newspapers and magazines from the economic field, semi-structured interviews, and balance sheets from 2012 to 2020. The space of the dominant dental equipment firms in Brazil was constituted of DabiAtlante, Gnatus, Alliage and Olsen, which have structured this space since the 1940s with the merger of DabiAtlante and Gnatus into Alliage, these have continued strong in the sector. The financial capital presents transformations between 2012 and 2020, with stable profit for Olsen and profits and losses in the rest. The important capital valued by the companies is their technological capital, namely their research, development and innovation capacity to compete in the market; their symbolic capital and their commercial capital, which requires further investigation. The relationship with the State, the organizations representative of the sector, the expansion of the distribution network, exports, and public sector demands warrant subsequent studies.